Blue-green emitting cationic iridium complexes with 1, 3, 4-oxadiazole cyclometallating ligands: synthesis, photophysical and electrochemical properties, theoretical investigation and electroluminescent devices1. Issue 36 (28th September 2015) - Wang, Zhen; He, Lei; Duan, Lian; Yan, Jun; Tang, Ruiren; Pan, Chunyue; Song, Xiangzhi
<x xml:space="preserve">Abstract</x> Oxadiazole-type cyclometallating ligands lead to blue-green-emitting cationic iridium complexes, showing piezochromism and good performances in LECs.